Innovazione tecnologica e sinergie tra soluzioni geospaziali Lo "scenario Intergraph" - Fiduccia, Andrea (GEOmedia, 2012)
Negli ultimi anni abbiamo potuto assistere all'espansione delle tecnologie per l'Informazione Geografica dall'originale ambito della cartografia numerica per la conoscenza del territorio (automated mapping) o per la gestione delle infrastrutture e delle reti tecnologiche (facility management) verso un dominio più ampio denominato "geospatial". Technological innovation and synergies between geospatial solutions. The "Intergraph's scenario".Geospatial is much more than GIS. We can understand the evolution of Geographic Information considering some new working groups and OWS demonstrations of Open Geospa-tial Consortium: Sensor Web Enablement, Sensor Fusion Ena-blement, Feature & Decision Fusion, Aviation, Emergency and Disaster Management, etc. Another point of observation is to analyze some brand new products of a multinational enterprise committed to the innovation like Intergraph Corporation. Part of Hexagon AB, Intergraph, Leica Geosystems and ERDAS are working together to leverage joint strengths in geospatial in-novation.Intergraph's Motion Video Exploitation solution leverages full motion video, giving analysts the ability to collect, analyze, and maximize the value of video assets.GeoMedia 3D is a GeoMedia add-on product that extends the functionality of Intergraph's geospatial solutions through an integrated 3D visualization and analysis environment. You can visualize, navigate, analyze, and interact with 3D data na-tively in GeoMedia.GeoMedia Smart Client delivers an enterprise geospatial plat-form engineered to support large numbers of users who are unable to operate full desktop products, but whose workflows need advanced geospatial functionality that cannot be sup-ported by Web mapping tools.G/Technology Fiber Optic Works 1.0 streamlines the management of fiber optic infrastructure for utilities, municipalities, agencies and communications companies who are implement-ing a public or private fiber network. Fiber Optic Works is a complete, enterprise-scalable design and asset management system that allows users to efficiently manage the circuit com-plexity of a geospatially dispersed fiber optic communications network infrastructure, all in one integrated system.